1998
DOI: 10.1080/08035259850157921
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of discontinuation of nasal-CPAP in stable preterm infants breathing room air

Abstract: This trial assessed the consequences of discontinuation of nasal-CPAP in stable preterm infants breathing room air. Eighty-eight infants with a mean gestational age of 29 (24-33) weeks and a mean birthweight of 1264 (665-2060)g, randomized to either discontinuation of CPAP or its continuation, were clinically observed and monitored for 6 h by cardiorespiratory monitor, pulse oximeter and transcutaneous blood gas monitor. The abdominal circumference and gastric air and aspirate volumes were measured prior to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The weaning methods included sudden removal of NCPAP with or without oxygen supplementation, gradual increase in time off NCPAP, gradual reduction of pressure followed by removal of NCPAP, or a combination of these methods. [1925] …”
Section: Introductionmentioning
confidence: 99%
“…The weaning methods included sudden removal of NCPAP with or without oxygen supplementation, gradual increase in time off NCPAP, gradual reduction of pressure followed by removal of NCPAP, or a combination of these methods. [1925] …”
Section: Introductionmentioning
confidence: 99%
“…The standard deviation was assumed to be 0.13 [22] . Outcome data were analyzed by 'intention-to-treat'.…”
Section: Discussionmentioning
confidence: 99%
“…Sufficient compromise of pulmonary blood flow may actually worsen ventilation/perfusion mismatch and impair oxygenation [1719]. Gastric distension [20] – so-called “CPAP belly” – may aggravate feeding intolerance and provoke gastroesophageal reflux, itself a risk factor for ongoing lung injury [21,22]. Prolonged CPAP use may delay initiation of oral feeds, prolong hospitalization, limit infant holding, and constrain developmental therapies [23].…”
Section: Benefits and Harms Of Cpapmentioning
confidence: 99%
“…Our review of the literature identified three observational studies [27,32,33] and eight small to medium-sized randomized trials [20,34–40]. Neither of two systematic reviews [28,41] with differing objectives and study inclusions pooled data for meta-analysis due to low data quality and trial heterogeneity.…”
Section: Duration Of Cpap Support: Available Evidence For Best Pramentioning
confidence: 99%
See 1 more Smart Citation